ACCEPTANCE OF COOKIES PRODUCTS SUBSTITUTE OF PURPLE SWEET FLOUR, BIT AS A FOOD CONTAINS IRON - Afrinia Eka Sari; Salwa Salsabillah; Tria Maulida Ahadiyati; Rahmanita Pujianti (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
One of the anemia prevention programs for young women is the provision of blood-added tablets, but this program has not been running effectively. Apart from coming from primary food sources and TTD, efforts to increase iron intake can be made by consuming snacks. One of the favorite foods among young women is cookies. This study aims to analyze the organoleptic test of making cookies substituted with purple sweet potato flour and beetroot as an alternative snack to prevent anemia in adolescent girls. Experimental research with a completely randomized design consisting of three factors, namely wheat flour, purple sweet potato flour, and beetroot juice, with three treatments with a ratio of 150 gr, 100 gr, 125 gr flour, purple sweet potato flour, 50 gr, 10 gr, 75 gr, and beet juice 5 gr, 10 gr, 15 gr. 30 untrained panelists conducted this study. The sensory analysis found that formula 2 was superior, while hedonic analysis found that formula one was preferred. Cookies with purple sweet potato flour substitution with the addition of beetroot juice have significant differences in sensory characteristics (organoleptic) in terms of color, aroma, taste, and texture.